2022
DOI: 10.5812/jjcdc.123080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perceived Social Support, Spiritual Well-being, Health Literacy, and Resilience on Quality of Life in Patients Undergoing Hemodialysis: A Structural Equation Model

Abstract: Background: Spiritual well-being, social support, health literacy, and resilience may affect the quality of life (QOL) in patients undergoing hemodialysis. Objectives: The purpose of this study was to investigate the effect of perceived social support, spiritual well-being, health literacy, and resilience on the QOL in patients under hemodialysis. Methods: This descriptive cross-sectioanl study randomly included 260 patients from three educational hospitals in Ahvaz, Iran. Data were collected using a 36-item Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(44 reference statements)
0
3
0
2
Order By: Relevance
“…One of the few studies to explore spiritual well-being among people experiencing homelessness found that religiousness and spirituality were important factors in the lives of men and women experiencing homelessness, and both religiousness and spirituality were associated with lower suicidal ideation ( Vitorino et al ., 2021 ). A few studies have explored the association between HL and spiritual well-being in different populations, such as maternal HL among women ( Khorasani et al ., 2022 ), or patients living with kidney disease (undergoing haemodialysis) ( Hassani et al ., 2022 ). Moreover, earlier research has emphasised the need to increase social support to promote spiritual issues, specifically, the meaning of life among women with breast cancer ( Jadidi and Ameri, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies to explore spiritual well-being among people experiencing homelessness found that religiousness and spirituality were important factors in the lives of men and women experiencing homelessness, and both religiousness and spirituality were associated with lower suicidal ideation ( Vitorino et al ., 2021 ). A few studies have explored the association between HL and spiritual well-being in different populations, such as maternal HL among women ( Khorasani et al ., 2022 ), or patients living with kidney disease (undergoing haemodialysis) ( Hassani et al ., 2022 ). Moreover, earlier research has emphasised the need to increase social support to promote spiritual issues, specifically, the meaning of life among women with breast cancer ( Jadidi and Ameri, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that strong belief among the hemodialysis patient is correlated with decreased perception of illness burden and increased perception of social support. 2 So religious feelings should be added to this research as they are originally discussed under the domain of WHO-QOL BREF to assess the level of depression among the patients.…”
Section: Dear Editormentioning
confidence: 99%
“…Dalam kesempatan FGD yang dilaksanakan, para peserta dapat saling terbuka dalam menyampaikan permasalahan-permasalahan yang dihadapi selama pandemi Covid-19 yang semakin menantang, berat, dan penuh ketidakpastian. Hasil identifikasi permasalahan menunjukkan bahwa mayoritas pasien lupus mengalami masalah biologis, psikologis, dan sosial, Artinya penanganan secara holistik perlu diberikan untuk mengatasi permasalah yang dihadapi pasien lupus dan keluarga di Yayasan Kupu Parahita Indonesia (Adams et al, 2014;Hassani et al, 2022;Torres-Soto et al, 2022). Oleh karena itu, rancangan kegiatan pengabdian kepada masyarakat diarahkan untuk memecahkan masalah dengan pemberian dukungan secara holistik, baik dari segi biologis, psikologis, sosial, dan spiritual (Cacciatore et al, 2021;Onyishi et al, 2022;Peña-Vargas et al, 2021;Seiler et al, 2020).…”
Section: Pembahasanunclassified
“…Harapan dibuatnya film cerita ini adalah dapat dijadikan bekal bagi pasien-pasien lupus yang baru saja didiagnosis lupus agar tetap semangat menjalani pengobatan dan perawatan serta diet yang tidak mudah. Dengan demikian, film cerita ini diharapkan dapat menjadi sarana optimalisasi dukungan sosial bagi pasien lupus dan keluarga, khususnya pasien lupus yang baru didiagnosis baik di Indonesia maupun di Yayasan Kupu Parahita Indonesia (Beach et al, 2008;Fathoni et al, 2022;Ghafoor et al, 2022;Hassani et al, 2022;Onyishi et al, 2022;Rahayu & Yona, 2019). Beberapa penelitian sebelumnnya menyatakan bahwa pemberian dukungan social pada pasien lupas dapat memoderasi penerimaan diri dan rasa syukur (Dienillah & Chotidjah, 2021).…”
Section: Pembahasanunclassified